Evaluation of prostheses retained zygomatic and dental implants in large defects in the maxilla due to tumors or major trauma by biomechanical 3- dimensional finite element analysis - Hatice Yemenoglu; Melek Beder; Murat Yaylacı; Ayberk Dizdar; Murat Alkurt; Muhammed Enes Naralan; Ecren Uzun Yaylacı; Mehmet Emin Özdemir; Şevval Öztürk; Zeynep Yeşil (BMC Oral Health)
Abstract Background Zygomatic implants are becoming an ideal treatment approach for implant-supported prosthesis treatment developed for the atrophic maxilla. This study aims to evaluate the amount and distribution of stress in implants and peri-implant bone using different implant-supported prosthesis configurations in Aramany Class I maxillary defects through 3-dimensional finite element analysis. Methods A 3-dimensional finite element model of the Aramany class I defect was created. Three different implant-supported prostheses were modelled: model 1: 1 zygomatic implant and 3 dental implants, model 2: 1 zygomatic implant and 2 dental implants, and model 3: 2 zygomatic implants. Vertical and horizontal loads of 150 N were applied in 6 different ways to the defected and non-defective areas. Maximum principal stress and von mises stresses in the bone surrounding the implants were evaluated. Results When all loading conditions were evaluated with both porcelain layer on Co-Cr framework and acrylic layer on acrylic framework, the highest maximum principal stress value was observed in Model 3. In contrast, the lowest value was observed in Model 1. The highest maximum principal stress occurred when a horizontal load was applied simultaneously to both the defective and non-defective areas. In contrast, the lowest value was observed when a vertical load was applied to the non-defective area. The von Mises stress values were found to be similar across all models when both restoration materials were used. Conclusions Based on the results of this study, it can be concluded that increasing the number of implants in the non-defective area reduces the highest stress value while using acrylic as a restoration material slightly increases the stress value.